Commercial protectionism as a response to the globalization crisis in the West: Trump and Brexit - Medina Rivas Plata, Anthony Rolando (Ius Humani. Jornal do direito, 2024)
In recent years, we have witnessed a significant turn towards commercial protectionism as a response to what some perceive as clear discontent provoked by the current process of globalization. Our work will focus on two of the most emblematic events symbolizing this trend: the presidency of Donald J. Trump (2017-2021) in the United States and the Brexit referendum in the United Kingdom. Trump marked a turning point in U.S. trade policy, advocating an "America First" approach that included imposing tariffs and renegotiating international trade agreements. On the other hand, the 2016 Brexit referendum and the subsequent UK's departure from the European Union in 2020 represented a paradigmatic case of regional protectionism. Therefore, we will explore how Brexit affected trade relations between the UK and the EU, as well as its position on the international stage. Along these lines, we will discuss the broader implications of these two dynamics in the context of the globalization crisis: Do these movements pose a sustainable challenge to the existing global economic order, or are they temporary responses to specific issues? What lessons can be drawn from these experiences for the future management of trade conflicts?